Dampak Kualitas Air Pada Budi Daya Ikan Dengan Jaring Tancap Di Desa Toulimembet Danau Tondano - Urbasa, Pilipus A; Undap, Suzanne L; Rompas, Robert J (Universitas Sam Ratulangi, 2015)
In this study, we determined the current condition of the water quality of Lake Tondano in terms of physical and chemical parameters in a fish farming locations on Lake Tondano of Toulimembet village waters. Determination of sampling points at each station is placed vertically at three predetermined points from the guard house toward the front of the net, the distance between one point to the next point was Â± 12 m; whereas for the analysis of water quality parameters was done using an HORIBA water quality meters type U-536. Determination points were done by purposive sampling which refers to the physiographic location wherever possible in order to represent or describe these waters. The research was carried out for 3 weeks and was done in 3 stages, morning, afternoon and evening. For direct measurement (in situ) was performed once a week at the three points which included parameters pH, temperature, conductivity, DO, Oxidation reduction potential, turbidity, TDS, depth and GPS. Generally, the result of water quality analysis at the aquaculture still in the water quality standard PP No.82 of 2001. Keywords: Water Quality, Stick Net Cage, Lake Tondano, Aquaculture